(untitled) (Italian Review of Legal History, 2024)
The essay analyzes the position of Giuseppe Codacci-Pisanelli (1913-1988), academic and constituent, on the issue of the introduction of the decree-law into the Constitution. The study offered focuses solely on the scientific story of Codacci-Pisanelli with respect to the theorization of necessity as a condition legitimizing the Government’s recourse to provisional measures with «the effect of ordinary law», then transfused into the assembly debate. The theory – attributable, in some ways, to the original and most significant expressions of the Italian school of public law founded by V.E. Orlando – does not suggest that necessity «can be interpreted as a source of law in itself»; however, it reveals one of those cases «in which particular and exceptional forms of juridical production must be admitted». Responding to the need to revive Codacci-Pisanelli’s juridical thought, the paper, at the end, relates the constitutional construction that was then determined in the Republican Constitution with the completed elaboration that brought to completion the drafting of art. 77 and the complex range of the phenomenon, both in the light of the requirements of the legislative procedure and of the relations between political-constitutional subjects.